A RARE CASE OF NECROTIZING FASCIITIS AND CELLULITIS OF THE BREAST: clinic case - Kasimov, U.K.; Sultanova, D.U.; Kosimova, M.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Necrotizing soft tissue infections is a formidable disease either presenting on its own or as a result of various manipulations. It is a potentially fatal condition that usually affects the soft tissues of the extremities, abdominal wall and perineum. However, the condition can also manifest in other parts of the body. Predisposing factors include the presence of comorbidities, advanced age, and chronic alcoholism. The mammary gland is rarely affected, and, in most cases, it is a consequence of various manipulations, in particular puncture methods of treatment, inadequate conservative therapy, or trauma. The paper presents a clinical case of necrotizing fasciitis of the breast in a 29-year-old female patient with no identified risk factor and provides a therapeutic and diagnostic concept about necrotizing infection.